SONGS OF LONTAR PALM TAPPERS: SPIRITUAL, SOCIAL, AND CULTURAL EXPRESSIONS OF THE SABU RAIJUA COMMUNITY - Daniel H. Jacob; M. Yoesoef; Tommy Christomy (RADJA PUBLIKA, 2026)
Singing atop lontar palm trees (Alure Pa Kolo Due) is a traditional practice performed by sap tappers on Sabu Island, Sabu Raijua Regency, East Nusa Tenggara Province. These songs constitute a living form of oral tradition within the Sabu community. This study aims to explore the functions, meanings, and values embedded in these songs, particularly as expressions of spirituality, social relations, and cultural identity. Using a qualitative approach with descriptive-analytical methods, this research examines three lontar tapping songs (Alure Due) in terms of their textual and contextual dimensions. The findings reveal that, beyond serving as a means of entertainment and alleviating solitude during tapping activities, the songs function as a medium of social communication, a vehicle for cultural preservation, and an expression of the spiritual relationship between humans and nature—especially the lontar palm, which is regarded as a symbol of life. These songs encompass themes such as longing for homeland, pride in Sabu identity, filial devotion, moral reflection, and communal harmony. Analysis of the three songs indicates shared values of gratitude, hope, and social solidarity, despite variations in specific meanings. These findings support Vansina’s view that oral traditions function as mechanisms for transmitting cultural values and norms across generations.